LAND LEASE SYSTEM BETWEEN LAND OWNERS AND PT SUMBER ALFARIA TRIJAYA TBK IN CENTRAL LAMPUNG REGENCY FROM THE PERSPECTIVE OF SHARIA ECONOMIC LAW - Fuadi, As'ad; Mohammad Yasir Fauzi; Liky Faizal (Jurnal Dinamika Ekonomi Syariah, 2025)
ABSTRACT Humans as social creatures are a nature given by Allah SWT. For this reason, humans will need each other and cannot live alone to fulfill their daily needs. One of the basic needs for humans is wealth. The ways to obtain wealth are very diverse, ranging from trading, farming, and also service activities. The practice of muamalah can be carried out with various contracts. One of them which is still the people's choice is the rental or ijarah contract. Ijarah is an agreement to transfer the right to use goods or services, through the payment of rental wages, without being followed by a transfer of ownership of the goods. The formulation of the problem in this research is. What is the Practice of the Land Lease System from a Sharia Economic Law Perspective in Alfamart, Central Lampung Regency. This research is a research approach used, a qualitative approach, which means a research process based on a methodology that investigates a phenomenon or problem in society. The research approach used will produce descriptive data in the form of written or spoken words and the behavior of the person being observed. The type of research used in this research is a case study, in which the researcher carries out an in-depth investigation of a unit, organization, institution, or certain phenomenon which then produces a good, complete and detailed picture. The results of this research found The aim is to establish a good relationship with the location owner. Based on research conducted by researchers regarding the land rental system in Alfamart, Central Lampung Regency, it can be concluded that the land rental practice that has been agreed upon by both parties does not fulfill the pillars and conditions of the ijarah. So the contract that has been carried out can become void. Apart from not fulfilling the pillars and requirements of ijarah, the land rental that occurs at Alfamart Central Lampung Regency also does not fulfill the principles of Islamic economics, these principles are the principles of divinity (Divine), justice (Adl), prophethood (Al -Nubuwah), government (Al -Caliph), and results or profits (Ma'ad).